Model Online Marketing Facebook Ads Dalam Peningkatan Penjualan UMKM Kediri - Chiya Ratul Umah; Sutantri Sutantri; Iva Khoiril Mala (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research was conducted to determine the online marketing model using Facebook Ads implemented by Rumah Curasi as a Professional Curator. Applied to MSMEs under the guidance of the Curation House as an effort to advance the promotions carried out. Online promotion is a promotional method carried out using internet media such as Facebook, Whatsapp, and the like. The research method used is a field research method with a descriptive qualitative approach. The data used is primary data and secondary data. Primary data comes from interviews and official documents, while secondary data comes from supporting data found in the field. The results of the research carried out are that Rumah Curasi implements an online marketing model using Facebook Ads. The use of the online marketing model with Facebook Ads has quite potential, because Facebook is still a social media that is loved by many Indonesian people. By utilizing advertising on Facebook Ads, it is hoped that it can increase the sales volume of Kediri MSME products. Keywords : Facebook Ads , MSMEs , and Sales Volume .